2019
DOI: 10.1093/jee/toz090
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance and Realized Heritability of Resistance to Imidacloprid in the Brown Planthopper, Nilaparvata lugens (Hemiptera: Delphacidae), From Indonesia

Abstract: The brown planthopper, Nilaparvata lugens Stål., is a major insect pest causing serious damage to the rice crop in many rice-producing countries. The aim of the study was to determine the inheritance characteristics and realized heritability of resistance to imidacloprid in N. lugens from Banyumas, Central Java Province, Indonesia. The five generations of selection increased the resistance ratio (RR) from 46.20-fold at generation 45 (G45) to 150.39-fold (G49) compared with the laboratory-susceptible population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 38 publications
4
8
1
Order By: Relevance
“…The finding of dominance, or the otherwise intermediate expression of many detoxification genes in F1s as compared to parents (i.e., partial dominance or additivity), suggests that genetic variants underlying expression of xenobiotic resistance or host plant use associated genes should be visible to selection in female T. urticae mites (the diploid sex used in our study). This is consistent with the findings of a number of studies that have revealed that phenotypic resistance against pesticides often exhibits incomplete dominance contributed by multiple loci [89][90][91][92]. For spider mites, however, an additional factor that likely impacts rapid adaptation is that males are haploid, and in haploid individuals dominance relationships are not relevant.…”
Section: Dominance or Partial Dominance Is A Common Inheritance Patte...supporting
confidence: 89%
“…The finding of dominance, or the otherwise intermediate expression of many detoxification genes in F1s as compared to parents (i.e., partial dominance or additivity), suggests that genetic variants underlying expression of xenobiotic resistance or host plant use associated genes should be visible to selection in female T. urticae mites (the diploid sex used in our study). This is consistent with the findings of a number of studies that have revealed that phenotypic resistance against pesticides often exhibits incomplete dominance contributed by multiple loci [89][90][91][92]. For spider mites, however, an additional factor that likely impacts rapid adaptation is that males are haploid, and in haploid individuals dominance relationships are not relevant.…”
Section: Dominance or Partial Dominance Is A Common Inheritance Patte...supporting
confidence: 89%
“…The same results occurred in BPH from Karawang where RR increase by 13.5 folds in the 6 th generation (Iswanto et al, 2019). Resistance inheritances is autosomal, epigenetic not completely dominant, and not stabil (Diptaningsari et al, 2019;2020). Resistance monitoring is an essential effort to understand population susceptibility to several active ingredients as a management strategy to prevent insecticide resistances within pest populations (Zhang et al, 2016).…”
Section: Introductionmentioning
confidence: 60%
“…Resistance ratio against imidacloprid have been reported to increase to the next generation. Diptaningsari et al (2019) reported RR increase of 5 generations from Banyumas by 46.2 folds to 150.39 by the fifth generation. The same results occurred in BPH from Karawang where RR increase by 13.5 folds in the 6 th generation (Iswanto et al, 2019).…”
Section: Introductionmentioning
confidence: 97%
“…As one of the most serious pests of rice (one of the major grain crops for half of the world's population (Khush 1999), the brown planthopper causes considerable economic damage by feeding on rice plants and transmitting viruses associated with grassy stunt and ragged stunt diseases (Sōgawa 1982). These insects have developed resistance to selected pesticides (Wu et al 2017;Diptaningsari et al 2019). The brown planthopper shows wing dimorphism in both sexes: adults with fully developed wings, i.e., the macropterous form, and adults with truncated wings, i.e., the brachypterous form.…”
Section: Cabi Agriculture and Biosciencementioning
confidence: 99%